2010
DOI: 10.1021/ie901702h
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibrium in Extractive Distillation of the Acetone/Methanol System Using Water as Entrainer and Pressure Reduction

Abstract: Displacement of the azeotropic composition of acetone/methanol system by using water as entrainer has been studied for different solvent:feed molar ratios (S/F = 1.0, 2.5, and 3.0) combined with pressure reduction, at 75.0 kPa. The vapor−liquid equilibrium data were compared to ASPEN Plus simulations using Wilson, NRTL, and UNIQUAC models. To determine the composition of the liquid and vapor phases, headspace-gas chromatography was used. For a solvent:feed molar ratio of 1.0 was obtained a complete azeotrope e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The vapor–liquid equilibrium (VLE) of the system acetone–​methanol with water is described with the UNIQUAC thermodynamic model with the Aspen Plus built-in binary parameters while the ideal vapor phase is assumed. The reliability of the VLE model has been assessed by Botia et al using vapor–liquid equilibrium experimental data under atmospheric and vacuum pressure. Notice that the tray number is counted from top to bottom of the column, and the condenser is considered as the first tray.…”
Section: Background Method and Objective Functionmentioning
confidence: 99%
“…The vapor–liquid equilibrium (VLE) of the system acetone–​methanol with water is described with the UNIQUAC thermodynamic model with the Aspen Plus built-in binary parameters while the ideal vapor phase is assumed. The reliability of the VLE model has been assessed by Botia et al using vapor–liquid equilibrium experimental data under atmospheric and vacuum pressure. Notice that the tray number is counted from top to bottom of the column, and the condenser is considered as the first tray.…”
Section: Background Method and Objective Functionmentioning
confidence: 99%
“…The VLE data are obtained by using a modified equilibrium still similar to Othmer still , with some modifications described elsewhere. The modified equilibrium still and experimental procedure are described in detail in the previous work . This still can prevent the occurrence of violent boiling efficiently.…”
Section: Methodsmentioning
confidence: 99%
“…In order to model the vapor-liquid equilibrium for this mixture, the UNIQUAC model has been used [28]. It has been reported that the UNIQUAC model fits with vaporliquid equilibrium experimental data for the system acetone/ methanol/water [29]. In Fig.…”
Section: Extractive Distillation Sequencesmentioning
confidence: 99%